ANALISIS LAPORAN KEUANGAN DENGAN MENGGUNAKAN RASIO CAMEL DAN METODE ALTMAN SEBAGAI ALAT UNTUK MENGUKUR TINGKAT KESEHATAN USAHA PADA BANK RIAU KEPRI CAPEM PANAM - Fifi Nofianti; Gusnardi Gusnardi; Rina Selva Johan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrac : Banking problem in Indonesia is complicated. In the middle of 1997, when it was monetary crisis and performance of bank decreased. Banking monetary condition was related to the fall of Rupiah exchange rate toward US Dollar. This research aimed to find out business condition rate through CAMEL ratio and Altman method, it was also to compare the result of those methods. The data used was primary data that direct interview to employee and secondary data in form of report data. To analyze the healthiness of a company, this research used quantitative analysis. To analyze data, it used capital, asset, earning and liquidation analysis by Z-score formula. The result showed that Riau Bank was in good condition by using CAMEL ratio, while by using Altman method showed 1,84 which was in grey area. This was because the business that has been running by Riau Kepri Capem Panam was in small scale.Key word : Capital, Asset, Earning, Likuidasi, Altman Method